Are You Scared Yet? On the Ethic of Sustainability and the Politics of Fear in Public Administration. (2nd October 2017) - Spicer, Michael W.; Bowen, William M.
Abstract : This article offers a critical examination of the ethic of sustainability. It argues that, notwithstanding the importance of environmental problems, such an ethic has the effect of promoting a politics of fear by emphasizing our fears about human survival and security. As such, despite its attractions, an ethic of sustainability for public administration reinforces already deeply embedded antipolitical ways of thinking within the field that ignore its constitutional practices and traditions, and are potentially harmful to public administration practice.